Coupling nearshore and aeolian processes: XBeach and duna process-based models. (May 2019) - Roelvink, Dano; Costas, Susana
Abstract: A new dune profile model, Duna, is developed and coupled with the existing XBeach model, in which some key improvements allow a much better behaviour of the intertidal beach and the inclusion of structural erosion or accretion through a longshore transport gradient. The model is shown to represent typical behaviour of a beach-dune system in Praia de Faro, Portugal and to be able to simulate processes on a decadal timescale. The model captures a balance between longshore gradients and cross-shore processes in the surf zone, competing effects of moderate conditions and storms in the intertidal area and between build-up by storm waves and aeolian transport on the berm. Vegetation behaviour is shown to play a key role in the development of the shape of the foredunes. The relation between progradation or recession rate and foredune height as often reported in literature is reproduced and explained. Graphical abstract: Image 1024 Highlights: A coupled beach-dune profile model XBeach-Duna was developed. Berm building by storm waves is balanced by wind-blown erosion of the berm. The intertidal beach maintains a similar slope through moderate and storm conditions. Longshore transport gradients are balanced by cross-shore gradients in the surf zone. The height of the foredune decreases with increasing progradation rate.